Theology from Marginalized Experience: Humanistic Islam and Transgender Muslim Subjectivity in Indonesia - Muhammad Arif; Robby Habiba Abror; H. Zuhri (Islamika Inside: Jurnal Keislaman dan Humaniora, 2026)
This article examines how the religious experiences of waria (transgender Muslims) in Indonesia can articulate a Humanistic Islamic Theology centered on human dignity, justice, and ethical recognition. While previous studies have predominantly examined waria pesantren through sociological, educational, and gender perspectives, their implications for contemporary Islamic theology remain insufficiently explored. This study employs a qualitative, critical-hermeneutic inquiry based on a narrative-textual corpus, drawing primarily on Masthuriyah Sa'dan's Santri Waria (2020), complemented by scholarship in Islamic theology, lived religion, and gender studies. The corpus is examined through interpretive textual analysis to identify patterns of religious meaning, dignity, exclusion, and theological subject formation. The findings are interpreted through the ethical-emancipatory framework of Asghar Ali Engineer and Mohammed Arkoun's critique of epistemic closure in official Islamic discourse. The study finds that the Humanistic Islamic Theology cultivated within Pesantren Waria functions as a restorative religious space that reconstructs dignity through access to Qur'anic learning, ritual purification, congregational prayer, religious study, and communal solidarity, thereby enabling transgender Muslims to reclaim legitimate religious subjectivity despite enduring social and theological exclusion. Conceptually, this article contributes to contemporary Islamic theology by developing Humanistic Islamic Theology as an analytical framework that makes the lived religious experiences of marginalized Muslims legitimate sources of theological reflection, thereby expanding the ethical horizons of Islamic thought beyond juridical orthodoxy. These findings suggest that Islamic theology can be enriched by recognizing marginalized religious experience as a valid source of theological knowledge and by reorienting theological inquiry from legal conformity toward ethical recognition, human dignity, and social justice in contemporary Indonesia.